Pengembangan Teknologi Pengolahan Limbah Dan Pakan Fermentasi Untuk Mendukung Program PDB Di Desa Watu Kec. Marioriwawo, Kab. Soppeng, Sulawesi Selatan - Said, Muhammad Irfan; Utamy, Renny Fatmyah; Syawal, Sutomo; Said, Miah (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
There are two aspects of the problems of the cattle farming community in Soppeng Regency, namely the availability of feed and the impact of livestock waste. The largest waste potential in Soppeng Regency, especially Watu Village, is agricultural and livestock waste. However, it has not been utilized optimally. Watu Village, which is rich in organic materials, is one of the reasons for developing this village as an organic farming village in Soppeng Regency. The purpose of this activity is to increase the capacity of knowledge and skills of partner farmers in processing organic waste from livestock and agriculture to be produced into compost fertilizer or fermented feed (silage). A total of 3 community group partners were involved, namely: 1) the "Allaringnge" farmer/livestock group, 2) the "Kampung Baru" women's farmer group and 3) the village-owned business entity "Dewa Utama". Two technology packages have been applied to partners, namely compost production process technology and fermented feed (silage) production process technology. The applied technology method is carried out in four stages, namely: 1) socialization, 2) training, 3) practice and creation of technology demonstration plots, and 4) evaluation. The results of the implementation of the activities have proven to be able to increase the capacity and knowledge of partners regarding the methods and processes for producing organic fertilizer (bio-compost) and fermented feed (silage) by utilizing livestock and agricultural waste.